Post-transplant cyclophosphamide versus anti-thymocyte globulin in allogeneic hematopoietic stem cell transplantation from unrelated donors: A systematic review and meta-analysis - Tang, Lu; Liu, Zhigang; Li, Tao; Dong, Tian; Wu, Qiuhui; Niu, Ting; Liu, Ting; Ji, Jie (Frontiers in Oncology, 2023)
Background Post-transplant cyclophosphamide (PTCy) and anti-thymocyte globulin (ATG) are both common graft-versus-host disease (GVHD) prophylaxis strategies in allo-HSCT from unrelated donors. However, no consensus has reached on which regimen is optimal. Although several studies concerning this topic exist, the outcomes of different studies still conflict with each other. Therefore, an overall comparison of the two regimens is urgently needed to help make informed clinical decisions. Methods Studies comparing PTCy and ATG regimens in unrelated donor (UD) allo-HSCT were searched in four critical medical databases from inception to April 17, 2022. The primary outcome was grade II-IV aGVHD, grade III-IV aGVHD and chronic GVHD (cGVHD), and the secondary outcomes included overall survival (OS), relapse incidence (RI), non-relapse mortality (NRM), and several severe infectious complications. The quality of articles was assessed by the Newcastle-Ottawa scale (NOS), and data were extracted by two independent investigators and then analyzed by RevMan 5.4. Results Six out of 1091 articles were eligible for this meta-analysis. Compared with the ATG regimen, prophylaxis based on PTCy achieved a lower incidence of grade II-IV aGVHD incidence (RR=0.68, 95% CI 0.50-0.93, P=0.010, I2 = 67%), grade III-IV aGVHD (RR=0.32, 95% CI 0.14-0.76, P=0.001, I2 = 75%), NRM (RR=0.67, 95% CI 0.53-0.84, P=0.17, I2 = 36%), EBV-related PTLD (RR=0.23, 95% CI 0.09-0.58, P=0.85, I2 = 0%) and better OS (RR=1.29, 95% CI 1.03-1.62, P=0.0001, I2 = 80%). The cGVHD, RI, CMV reactivation and BKV-related HC showed no significant difference between the two groups (RR=0.66, 95% CI 0.35-1.26, P<0.00001, I2 = 86%; RR=0.95, 95% CI 0.78-1.16, P=0.37, I2 = 7%; RR=0.89, 95% CI 0.63-1.24, P=0.07, I2 = 57%; RR=0.88, 95% CI 0.76-1.03, P=0.44, I2 = 0%). Conclusion In the setting of unrelated donor allo-HSCT, prophylaxis based on PTCy can lower the incidence of grade II-IV aGVHD, grade III-IV aGVHD, NRM and EBV-related complication, achieve better OS compared to ATG-based regimen. And cGVHD, RI, CMV reactivation and BKV-related HC were comparable in the two groups.